Conjugation of Synthetic Polyproline Moietes to Lipid II Binding Fragments of Nisin Yields Active and Stable Antimicrobials - Deng, Jingjing; Viel, Jakob H.; Kubyshkin, Vladimir; Budisa, Nediljko; Kuipers, Oscar P. (Frontiers in Microbiology, 2020)
Coupling functional moieties to lantibiotics offers exciting opportunities to produce novel derivatives with desirable properties enabling new functions and applications. Here, five different synthetic hydrophobic polyproline moieties were conjugated to either nisin AB (the first two rings of nisin) or nisin ABC (the first three rings of nisin) by using click chemistry. The antimicrobial activity of nisin ABC + O6K3 against Enterococcus faecium decreased 8-fold compared to full-length nisin, but its activity was 16-fold better than nisin ABC, suggesting that modifying nisin ABC is a promising strategy to generate semi-synthetic nisin hybrids. In addition, the resulting nisin hybrids are not prone to degradation at the C-terminus, which has been observed for nisin as it can be degraded by nisinase or other proteolytic enzymes. This methodology allows for getting more insight into the possibility of creating semi-synthetic nisin hybrids that maintain antimicrobial activity, in particular when synthetic and non-proteinaceous moieties are used. The success of this approach in creating viable nisin hybrids encourages further exploring the use of different modules, e.g. glycans, lipids, active peptide moieties, and other antimicrobial moieties.